Aesthetic experience models human learning - Starr, G. Gabrielle (Frontiers in Human Neuroscience, 2023)
Aesthetic experiences may promote and enable learning and creativity by enhancing the ability to understand complexity and integrate novel information. Offering a theoretical framework for understanding the cognitive benefits of aesthetics, this paper argues aesthetic experiences are the necessary outcome of human learning, in which natural objects or artworks are evaluated in a multi-dimensional preference space. The brain-states underlying these experiences harness configurations of the apex transmodal neural systems, the default mode network, the central executive network, and the salience network, that may give information-processing advantages by recruiting high-power communication hubs.